Screening of immune biomarkers in different breeds of chickens infected with J subgroup of avian leukemia virus by proteomic - Fei Ye (Taylor & Francis Group, 2020)
Avian leucosis (AL) is a disease characterized by tumors and is caused by the avian leukosis virus (ALV). Because of the high variability of viruses and complex pathogenic mechanisms, screening and breeding J subgroup of ALV (ALV-J) resistant avian breeds is one of the strategies for prevention and treatment of AL, thus screening of significant immune markers is needed to promote the development of disease-resistant breeds. In this study, data-independent acquisition (DIA) technology was used to detect the DEPs of three breeds of chicken according to different comparison to investigate the potential markers. Results showed special DEPs for spleen development of each breed were detected, such as PCNT, DDB2, and ZNF62. These DEPs were involved in intestinal immune network used in production of IgA signaling pathways and related to immune response which can be used as potential markers for spleen development in different breeds. The DEPs such as RAB44 and TPN involved in viral myocarditis, transcriptional misregulation in cancer, and tuberculosis can be used as potential markers of spleen immune response after ALV-J infection in chickens. Pair-wise analysis was performed for the three breeds after the infection of ALV-J. The proteins such as RFX1, TAF10, and VH1 were differently expressed between three breeds. These DEPs involved in antigen processing and expression, acute myelogenous leukemia, and viral carcinogenesis can be used as potential immune markers after ALV-J infection of different genetic backgrounds. The screening of potential markers at protein level provides a strong theoretical research basis for disease resistance breeding in poultry.